Analysis of the Electric Double Layer Structure Formed in an Ionic Liquid Using Neutron Reflectivity. (12th May 2022) - Tamura, Kazuhisa; Akutsu-Suyama, Kazuhiro; Cagnes, Marina; Darwish, Tamim A.
Abstract : The ionic liquid/Si electrode interface was investigated using neutron reflectivity. We precisely elucidated the structure of the electrical double layer formed at 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)amide ([BMIM]TFSA)/Si(100) electrode interface with the orientation of the [BMIM]TFSA molecule using a partially deuterated [BMIM]TFSA. The results revealed that [BMIM]TFSA molecules form a layered structure. Cation and anion molecules are alternatingly stacked and molecules in the first three layers are horizontally oriented to the electrode surface at E = −1.2 V, i.e., on the negatively charged electrode surface. It was also revealed that the imidazole ring in [BMIM] cation is parallel to the electrode surface.